KAJIAN SEMANTIK PERISTILAHAN ADAT DALAM UPACARA PERKAWINAN BATAK TOBA - Ambarita, Getha Novianti; Simanjuntak, Hotma; Seli, Sesilia (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThis study focused on observing the traditional ceremony of Batak Toba marriage. The researcher focused this study on semantic studies with research problems in the form of terms, terminology, and the meaning of the terminology of the traditional wedding ceremony of Batak Toba. The researcher used qualitative research methods and descriptive research forms. The source of the data in this study is custom terminology in the traditional ceremonies of the Batak Toba marriage written by Marhulalan Sihombing and in the form of utterances spoken by several informants. The data in this study are terminology contained in the traditional marriage ceremony in the Batak Toba tribe, the form and meaning of terminology in the Batak Toba wedding ceremony in the pre-marriage, marriage, and post-marriage stages obtained from informants. The techniques carried out by researchers in collecting data in the field were proficient listening techniques, note and record techniques, documentary study techniques. Data collection tools used in this study are written documents (custom books), voice recording devices, question instruments, and images. The results of this study are: first, terminology in the traditional ceremony of the Batak Toba marriage, secondly, the form of the terminology of the traditional ceremony of the Batak Toba marriage is monomorphemis, polymorphemis, and phrases. Third, the meaning of customary law in the marriage ceremony of Batak Toba.Â Keywords: terminology, marriage ceremony, Batak Toba